Oregon State Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: 6101. Oregon State Building. Alaska-Yukon-Pacific Exposition. Seattle. 1909. Printed on verso: Portland Post Card Co. Portland, Ore and Seattle, Wash. Dear Sir: If you are interested in Refrigerating or Ice Machinery we would be pleased to have you inspect the Larsen-Baker Ice Machine we have installed in the Oregon State Building when you visit the A.Y.P. Exposition the coming summer. The Cold Storage Rooms containing the entire Oregon exhibit of Apples are cooled with this machine. Yours Respectfully, Phil L. Serwe & Co. Agents. Larsen-Baker Ice Machine Co. 305 Occidental Ave. Seattle. PH Coll 777 PPCC.6101a To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number